Impact of Online Gaming on the Academic Performance of DEBESMSCAT-Cawayan Campus Students - Ricky Capinig Gabrito; Roger Yatan Ibañez Jr.; Jacob Frederick Palabiano Velza (Scientific Journal of Informatics, 2023)
Purpose: This study investigated the effects of online gaming on the academic performance of students of DEBESMSCAT-Cawayan Campus.Methods: A descriptive research design was employed, and a survey questionnaire was distributed to 75 student online gamers who were selected through a census approach. Statistical analysis techniques such as frequency and percentage were used to analyze the data.Result: Mobile Legends was found to be the most popular game among the respondents. The majority of students spent 1-2 hours playing online games per day and incurred costs associated with gaming. However, most respondents believed that their gaming activities did not significantly hinder their ability to perform tasks in school or at home. The effects of online games on academic performance were perceived positively by the respondents. They believed that online gaming had a positive impact on test scores, overall grades, submission of school activities, time in studying, concentration in studies, participation in learning activities, interaction with people, interest in class discussions, willingness to go to school, and interest in school activities.Novelty: This study provided a comprehensive overview of the perceptions of students regarding the effects of online games on their academic performance. The study suggested that online gaming could have both positive and negative effects on academic performance, depending on how it was managed by students. The study also contributed to the existing body of knowledge on the subject and may have informed future research and interventions aimed at supporting students in managing their gaming activities while maintaining their academic performance.